Adaptive resistance to therapeutic PD-1 blockade is associated with upregulation of alternative immune checkpoints - Shohei Koyama (Nature Portfolio, 2016)
Blocking immune checkpoints is a promising strategy to treat lung cancer, but patients often become resistant to the therapy. Here, the authors analyse resistance in mouse models of lung cancer and show in mice and two patients, an increase in the expression of TIM3, which is also involved in the immune response to cancer.